Pembinaan UMKM melalui Pelatihan MSDM pada Usaha Minuman Pop Ice di Pekanbaru - Martha, Dewi; Wahab, Wirdayani; Andariyani, Ira Meike; Putri, Delfi Oktafiani (Universitas Pahlawan Tuanku Tambusai, 2026)
Micro, Small, and Medium Enterprises (SMEs) engaged in Pop Ice beverages in Pekanbaru, despite their high market potential, face significant challenges in internal management, particularly unstructured Human Resource Management (HRM). This Community Service (PkM) aims to address these HRM weaknesses, characterized by inconsistent service quality and high employee turnover, through managerial coaching. The methodology utilized is a combination of Public Education (Counseling), Practical Skills Training, and In-Situ Mentoring. The PkM results show significant achievements according to the established objectives: (1) An increase in HRM concept comprehension (measured by Post-tests), indicating partner awareness that operational issues stem from HR weaknesses. (2) Practical skills acquisition was realized through the development of Simple SOPs for product blending and service, along with training in performance feedback. (3) The realization of professionalism was confirmed by Observations and Interviews after mentoring, showing SOP implementation, increased work efficiency, and reduced customer complaints. In conclusion, structured and application-based HRM intervention is crucial for strengthening the internal foundation of SMEs, ensuring consistent service quality, and enhancing professionalism. This outcome is essential for business sustainability and retaining customer loyalty.